2017
DOI: 10.3897/zookeys.663.11415
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assessment of three species of Anilocra (Isopoda, Cymothoidae) ectoparasites from Caribbean coral reef fishes, with the description of Anilocra brillae sp. n.

Abstract: A morphological review and molecular characterization of Anilocra haemuli Bunkley Williams & Williams, 1981, were completed using specimens collected from Haemulon flavolineatum Desmarest, 1823 (French grunt) and Epinephelus guttatus Linnaeus, 1758 (red hind). Molecular and morphological data suggest that the isopods parasitizing H. flavolineatum and E. guttatus are different species. The specimens collected from E. guttatus are recognized as a new species, Anilocra brillae sp. n. Differences between Anilocra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Nearly half of the species of Anilocra accepted today were described in the 1980s, with many originating from the Indo-Pacific and Caribbean [8, 21]. Since 2001, just four new species have been described based on material from the Caribbean [24], Chile [25], Lebanon [26] and the Gulf of Mexico [27]. In 2017, using morphological and molecular data, Anilocra brillae [24] from the Caribbean was identified and described based on specimens that were originally thought to be Anilocra haemuli [8].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nearly half of the species of Anilocra accepted today were described in the 1980s, with many originating from the Indo-Pacific and Caribbean [8, 21]. Since 2001, just four new species have been described based on material from the Caribbean [24], Chile [25], Lebanon [26] and the Gulf of Mexico [27]. In 2017, using morphological and molecular data, Anilocra brillae [24] from the Caribbean was identified and described based on specimens that were originally thought to be Anilocra haemuli [8].…”
Section: Resultsmentioning
confidence: 99%
“…Since 2001, just four new species have been described based on material from the Caribbean [24], Chile [25], Lebanon [26] and the Gulf of Mexico [27]. In 2017, using morphological and molecular data, Anilocra brillae [24] from the Caribbean was identified and described based on specimens that were originally thought to be Anilocra haemuli [8]. This revision is an example of the cryptic nature of some Anilocra spp., and the importance of combining morphological and molecular data whenever possible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…may also form dense schools and show demersal behavior, but they mainly feed in rocky areas, preying on epifaunal organisms or feeding on macroalgal tissue, respectively (Garc ıa-Charton et al, 2004). On the other hand, it should be also noticed that recent studies have revealed the existence of cryptic species within several cymothoid species (including some Anilocra species) with a wide diversity of potential hosts (Poore & Bruce, 2012;Welicky et al, 2017b).…”
Section: Discussionmentioning
confidence: 99%